COVID-19 and heat illness in Tokyo, Japan: Implications for the Summer Olympic and Paralympic Games in 2021 - Shimizu, K.; Gilmour, S.; Mase, H.; Le, P. M.; Teshima, A.; Sakamoto, H.; Nomura, S. (International Journal of Environmental Research and Public Health, 2021)
The 2020 summer Olympic and Paralympic Games in Tokyo were postponed to July-September 2021 due to the coronavirus disease 2019 (COVID-19) pandemic. While COVID-19 has emerged as a monumental health threat for mass gathering events, heat illness must be acknowledged as a potentially large health threat for maintaining health services. We examined the number ofCOVID-19 admissions and the Tokyo rule for emergency medical care, in Tokyo, from March to September 2020, and investigated the weekly number of emergency transportations due to heat illness and weekly averages of the daily maximum Wet Bulb Globe Temperature (WBGT) in Tokyoin the summer (2016-2020). The peak of emergency transportations due to heat illness overlapped the resurgence of COVID-19 in 2020, and an increase of heat illness patients and WBGT has beenobserved. Respect for robust science is critical for the decision-making process of mass gatheringevents during the pandemic, and science-based countermeasures and implementations for COVID-19will be warranted. Without urgent reconsiderations and sufficient countermeasures, the doubleburden of COVID-19 and heat-related illnesses in Tokyo will overwhelm the healthcare provisionsystem, and maintaining essential health services will be challenging during the 2021 summer Olympic and Paralympic Games.